2001
DOI: 10.1039/b108207h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly ordered mesoporous polymer networks

Abstract: Synthesis of highly ordered three-dimensionally interconnected mesoporous hydrocarbon polymer networks exhibiting Bragg X-ray diffraction is reported by replicating the mesoporous MCM-48 and SBA-15 channel frameworks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 18 publications
1
62
0
Order By: Relevance
“…This was carried out by in situ polymerization as reported by Kim et al [21]. Briefly, a precursor solution of divinylbenzene (DVB) (Aldrich) with a free radical initiator, 1,1′-azobis(cyclohexane-carbonitrile) (ACC) (Aldrich) (DVB/ACC mol ratio: 12) was added dropwise until the structural porosity of the composite was filled up to the desired level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was carried out by in situ polymerization as reported by Kim et al [21]. Briefly, a precursor solution of divinylbenzene (DVB) (Aldrich) with a free radical initiator, 1,1′-azobis(cyclohexane-carbonitrile) (ACC) (Aldrich) (DVB/ACC mol ratio: 12) was added dropwise until the structural porosity of the composite was filled up to the desired level.…”
Section: Methodsmentioning
confidence: 99%
“…In a pioneering work, Johnston et al [2] reported on the preparation of ordered mesoporous polymers by using colloidal silica crystals as templates. Kim et al [3] synthesized highly ordered three-dimensionally interconnected mesoporous polymers by using mesostructured MCM-48 and SBA-15 silica materials as templates. Lee et al [4] employed a mesocellular silica foam as template to fabricate a porous polymer containing a bimodal porosity made up of two pore systems of sizes centred at 3 nm and 17 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a large number of ordered mesoporous materials with various compositions and structures have been successfully synthesized, including two-dimensional (2-D) hexagonal or/and 3-D cubic mesostructured silicates [7][8][9], metal oxides [10], metal sulfides [11], metals [12], polymers, and carbons [13][14][15][16]. In addition, further modification of these mesostructures can endow the materials with additional physicochemical functions, and therefore improve their performance in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] It is, however, much more difficult to design mesoporous organic materials (i.e., with pores in the range of 2-50 nm). Generally, mesoporous materials such as silica are synthesized through a soft templating approach, [13][14][15][16][17] whereas carbons or polymer networks usually require the use of silica-based hard templates, [1,[18][19][20] but some reports with a soft templating approach were recently reported as well. [21][22][23] Although this methodology led to interesting materials, it is practically a ''no-go'' for industrial applications because of its complexity and high cost.…”
mentioning
confidence: 99%